International Economic Relations, Institutional Isomorphism and Democracy in Latin America. Explaining the [Unexpected?] Convergences between Uruguay, Brazil and Honduras - Lopes, Dawisson Belem (Dados (Rio de Janeiro), 2007)
Along this article, we sought to apprehend the logic underlying the triangular relation between international economic powers, structural reforms of the State, & democracy in Latin America. The study is based on the findings expressed in the Report on "A Democracia na America Latina: Rumo a uma Democracia de Cidadas e Cidadaos" ["Democracy in Latin America: Towards a Democracy of Female & Male Citizens"] (PNUD, 2004). The data subject to scrutiny refer to three States -- Uruguay, Brazil & Honduras. Two hypotheses have been tested: (1) structural reforms of the State in Latin America have been conditioned by the dynamics of the international economy; & (2) the democracy that is possible in Latin America is a formalist democracy, & it does not inhibit the rational choice of market oriented economic agents. The conclusions of this work are discussed in the light of political theories & international relations. Tables, Figures, References. Adapted from the source document.